PERSEPSI INTERNAL AUDITOR TENTANG PENGARUH KUALIFIKASI INTERNAL AUDITOR TERHADAP PENERAPAN STRUKTUR PENGENDALIAN INTERN PADA BANK UMUM PEMERINTAH CABANG BANDUNG - Wiwi Idawati (Universitas Bunda Mulia, 2017)
Purpose of this research is to empirically examine internal audit qualification that consist of: (1) Independence, (2) Professional skill, (3) Network Audit, (4) The implementation of audit activity, (5) Management of Internal Audit Department, (6) Work Experience, (7) The number of Internal Audit Staff, (8) Management Support, and (9) Audit Technology, the influence to the application of internal control structure.This research was done at the government owned commercial banks Bandung branch. The data was collected by giving questionnaire the chairman and staff of internal control. The method was used in this research was survey method, that is collecting technique and data analysis like opinion from the respondent through questionnaire and interview. To facilitate the analysis and the hypothetical tests, path analysis model was as used of 10.0 SPSS. The result of this research indicated that variables of the internal audit qualification have positive influential to the application of internal control structure in the amount of 99,73% and 0.27% from other variable out of this research. Partially indicated that: only three variable was not significant to the application of internal control structure to the government owned commercial banks Bandung branch, that consist of network audit, the number of audit staff , and audit technology, where as six of free variable: Independence, Professional skill, the implementation of audit activity, Management of Internal Audit Department, work experience, and Management Support , have significant influence to the application of internal control structure to the government owned commercial banks Bandung branch. Independence variable is the most influence variable to the application of internal control structure.Key words : Internal auditor, internal control structure